Energy consumption, CO2 emission and economic growth: empirical evidence for Malaysia. (9th July 2019) - Sarkar, Md. Sujahangir Kabir; Al-Amin, Abul Quasem; Mustapa, Siti Indati; Ahsan, Md. Rajibul
This study focuses on the relationship among the energy consumption, carbon emission and economic growth of Malaysia by using a time series data from 1980-2016. The study findings are shown by an econometric analysis that energy consumption, total and per capita CO2 emission and gross domestic product (GDP) has increased vastly between 1980 and 2016. The Johansen cointegration test confirms the existence of the long run relationship of energy consumption with carbon emission and economic growth. Moreover, the Granger causality test reveals the unidirectional causality of energy demand and population with carbon emission. The positive and significant relationship between GDP and carbon emission is a critical issue in Malaysia that needs to be addressed with care as economic growth is necessary but increase of carbon emission is undesirable. Therefore, this study recommends to promote green energy, green growth (GDP) that will ensure both energy security and energy sustainability in Malaysia over time.